“Profplan”: Konsep Aplikasi Perencanaan Laba Metode Cost-Volume-Profit (CVP) Sebagai Peningkatan Profitability UMKM Di Indonesia - Ivo Rajava Fiba; Resha Dwi Ayu Pangesti Mulyono S.E., MA.Ak.; Kanzulia Arsyta Qaribil Hasanah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This research aims to develop a conceptual design for a profit planning application using Cost Volume Profit (CVP) analysis for Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a crucial role in Indonesia's economic growth, but they still face funding issues and a lack of guidance in financial planning and management. Therefore, optimizing profit generation becomes essential in strengthening the contribution of MSMEs to the economy. Cost Volume Profit (CVP) analysis is chosen as an effective profit planning method as it connects production costs, production volume, and profit. In this study, the author proposes the design concept of an application called "Profplan" specifically tailored to assist MSMEs in maximizing business profitability. This application will provide educational features such as short videos explaining fundamental accounting concepts related to manufacturing MSMEs. Furthermore, the application includes cost calculation and pricing determination features. The cost calculation feature helps users identify fixed and variable costs associated with production. Users can fill in a digital form with the costs incurred for production and obtain accurate production cost reports. The pricing determination feature utilizes the cost-plus pricing method with a full costing approach. Users can input their desired profit margin, and the application will recommend a selling price based on the production costs and the specified profit margin. The development of this application involves the collaboration of programmers and application developers. The steps include system design, application programming, usability testing, and patent registration before its official launch on the PlayStore and AppStore. With the "Profplan" application, MSMEs are expected to engage in profit planning more easily and effectively. This user-friendly approach will assist MSMEs in improving business profitability and contributing to Indonesia's economy.